KARAKTERISASI GAMBUT DENGAN BERBAGAI BAHAN AMELIORAN DAN PENGARUHNYA TERHADAP SIFAT FISIK DAN KIMIA GUNA MENDUKUNG PRODUKTIVITAS LAHAN GAMBUT - Iwan Sasli (Agrovigor, 2011)
This study aimed to obtain information about physical and chemical characteristics of the peat due to addition of ash ameliorant with different dosage to get the best growth media. Ameliorant materials are litter ash / vegetation result of peatlands clearance, rice husk ash and palm bunch ash. This study used split plot design consists of two factors, ameliorant factor (A) as main plots, with 4 levels (a1 = litter ash / vegetation result of peatlands clearance, a2 = rice husk ash, a3 = trapalm bunch ash), and ameliorant dose (D) with 5 levels (d0 = no ameliorant / control, d1 = 50 g ameliorant, d2 = 100 g ameliorant, d3 = 150 g ameliorant, D4 = 200 g ameliorant / tube of peat), treatment was repeated three times and consisted of two samples, so there are 90 units of treatment. Observations were done on the weight of the content (bulk density), density of type (particle density), total soil pore space, nutrient levels of N-total, P, K, Mg, and pH of soil. The results showed that the addition of ameliorant material significantly improve the availability of P, K, Mg, and pH of the soil, but decrease N concentration of peat. Peat soil treated palm bunch ash has a greater density lindak with total soil pore space smaller than the peat treated litter ash/ vegetation peat and rice husk ash.